2018
DOI: 10.1186/s12886-018-0908-x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of endogenous endophthalmitis with extensive subretinal abscess: a case report

Abstract: BackgroundEndogenous endophthalmitis could lead to a devastating outcome without a prompt and appropriate management. We report a case of advanced endogenous Klebsiella pneumoniae endophthalmitis with extensive subretinal abscess that was successfully treated with a vitrectomy.Case presentationA systemically well 61-year-old man complained of ocular pain and visual decrease in his right eye for eighteen days. Ophthalmic examination showed dense inflammation in the anterior chamber and vitreous body. Systemic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Due to the relatively small number of case series in most reports, there are not yet any guidelines on the management of this disease [9, 11, 12]. The therapeutic approaches and effects vary substantially among different reports and studies [10, 13, 14]. One decision tree analysis showed that the presence of K. pneumoniae was an independent factor associated with poor ocular outcomes of EE [15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively small number of case series in most reports, there are not yet any guidelines on the management of this disease [9, 11, 12]. The therapeutic approaches and effects vary substantially among different reports and studies [10, 13, 14]. One decision tree analysis showed that the presence of K. pneumoniae was an independent factor associated with poor ocular outcomes of EE [15].…”
Section: Introductionmentioning
confidence: 99%
“…The patient was treated with intravitreal ceftazidime, PPV, retinotomy and retinal abscess drainage. But the patient’s visual outcome was only HM [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…13 There is no clear consensus regarding the treatment of subretinal abscesses, and management is generally individualized for the patient's presentation. 5 Commonly used first-line treatment options for bacterial subretinal abscess include systemic antibiotics with intravitreal antibiotic injections. Additional options include pars plana vitrectomy with intravitreal antibiotics with or without retinotomy or retinectomy to drain the abscess.…”
Section: Discussionmentioning
confidence: 99%